P818 Venous thromboembolism is rare among hospitalised patients with an inflammatory bowel disease flare: a multicentre retrospective cross-sectional study. (15th January 2020) - Khoury, T; Shafrir, A; Kalisky, I; Safadi, M; Mari, A; Mahamid, M; H Katz, L; Kadah, A; Sbeit, W
Abstract: Background: Inflammatory bowel disease (IBD) patients have twice the risk of venous thromboembolism (VTE) compared with healthy controls. VTE can occur at both hospitalisation and after discharge. We aimed to assess the prevalence of VTE among IBD patients who were hospitalised with disease flare at three Israeli Hospitals. Methods: A retrospective cross-sectional analysis including all IBD patients who were admitted with disease flare at Galilee Medical Center, EMMS Nazareth Hospital and Hadassah Medical Center. Exclusion criteria were patients with confirmed diagnosis of hypercoagulable state or patients on drugs with pro-coagulable potential. Results: Eighty-one patients with overall 114 admissions were included in the study. The average age was 42.2 ± 18.5 years. Sixty-six patients (57.9%) were males. Forty-five admissions (39.5%) were due to ulcerative colitis (UC) flare and 69 admissions (60.5%) were secondary to Crohn's disease (CD) flare. Twenty-eight patients (24.6%) were smokers. Twenty-five patients (21.9%) and 39 patients (34.2%) were on recent biological and steroid treatment (within 3 months). The mean C-reactive protein and albumin levels at the day of discharge were 4.2 ± 4.6 mg/dl (normal range 0–0.5) and 3.5 ± 0.7 g/dl (normal values above 3.2), respectively. During hospitalisation, 57 (50%), 55 (48.2%), 29 (25.4%), 19 (16.7%) and 8 (7%) patients were treated with intravenous steroids, antibiotics, amino-salicylates, surgery and immunomodulators, respectively. Only four patients (3.5 %) were on prophylactic subcutaneous anticoagulation (enoxaparin) throughout their hospital stay and only 1 patient (0.9%) who have not been on anticoagulation developed in-hospital symptomatic VTE episode. Notably, this patient suffering from CD with ileo-colonic involvement developed subclavian vein thrombosis two day after PICC line insertion for total parenteral nutrition to optimise his nutritional state before performing surgery. The mean hospitalisation length was 6.5 ± 6.6 days. Conclusion: In-hospital VTE was rare among our IBD patients admitted with disease flare. In fact, the only one VTE event reported in our cohort is probably related to the PICC line insertion and not related to IBD flare. Notably undergoing surgery in our cohort was not correlated with VTE episodes. Further studies are warranted to characterise IBD patients at risk for VTE, to assess the risk factors for in-hospital VTE development and to address further the role of prophylactic anticoagulation among hospitalised IBD patients, mainly those with bloody diarrhoea.